Use of sevelamer in chronic kidney disease: beyond phosphorus control - Laura Rodríguez-Osorio; Diana Pazmiño Zambrano; Carolina Gracia-Iguacel; Jorge Rojas-Rivera; Alberto Ortiz; Jesus Egido; Emilio González Parra (Nefrología (English Edition), 2015)
Sevelamer is a non-calcium phosphate binder used in advanced chronic kidney disease (CKD) and in dialysis for hyperphosphataemia control. Several experimental, observational studies and clinical trials have shown that sevelamer has pleiotropic effects, beyond hyperphosphataemia control, including actions on inflammation, oxidative stress, lipid profile and atherogenesis, vascular calcification, endothelial dysfunction and the reduction of several uremic toxins. This is the biological basis for its global effect on cardiovascular morbidity and mortality in patients with chronic kidney disease. This review focuses on these pleiotropic actions of sevelamer and their impact on cardiovascular health, with the experience published after more than ten years of clinical expertise.